Religion, Support of Equal Rights for Same-Sex Couples and the Australian National Vote on Marriage Equality - Bouma, G; Perales, F; Campbell, A (My University, 2018)
In 2017, the Australian Government commissioned a national vote on same-sex marriage legislation, which elicited substantial debates dominated by religious voices. We examine the associations between religious identification, the importance of religion to one’s life and frequency of attendance at religious services and support for same-sex couples in such a unique context. We contribute to knowledge by (1) systematically examining these relationships in a country other than the United States (Australia) using high-quality, nationally representative panel data spanning 2005–2015 (Household, Income and Labour Dynamics in Australia Survey; n = 44,794 observations/18,384 individuals), (2) assessing the degree of intra-group heterogeneity in views toward equal rights, and (3) considering how religiosity modifies the effects of other sociostructural factors. We find high degrees of between- and within-group heterogeneity in support of equal rights for same-sex couples, and large religiosity gradients. Furthermore, religiosity suppresses the liberalizing effects on attitudes of historical time, education, socioeconomic background, and city residence.
Sociology of Religion
Keywords: Relationships; Beliefs and Values -- Religious; Families and relationships; Beliefs and Values; Relationships; Religious; Families and relationships